Development of Biodiversity E-Module Based on Local Potentials in Labuhanbatu Utara Regency to Train Science Literacy of High School Students - Nurul Azmi; Sri Ngabekti; Margareta Rahayuningsih (Journal of Innovative Science Education, 2023)
The local potential of North Labuhanbatu Regency is very diverse, which has the potential as a source of learning on biodiversity material to develop scientific literacy needed in 21st-century learning. Scientific literacy enables students to apply science in everyday life, not just understanding science in concepts. This study aims to produce local potential-based electronic modules in North Labuhanbatu Regency that are feasible based on validity, readability, and effectiveness to train students' scientific literacy. This research is a research and development (R&D) with a 4-D development model and a one-shot case study research design. Based on the results of the validation test, a percentage score of 94.22% was obtained, including the very valid category. The readability results obtained a score of 89.66 which indicates excellent legibility. Posttest results showed an average of 81.81 with an average classical completeness of 84.05%, including in the excellent and effective category. Based on these results the development of a biodiversity electronic module based on local potential in North Labuhanbatu Regency was declared feasible based on validity, readability, and effectiveness as teaching materials.